Productivity Dispersion, Between‐Firm Competition, and the Labor Share - Gouin-Bonenfant, Émilien (Econometrica, 2022)
I study the effect of labor market imperfections on the labor share in a tractable model that emphasizes the interaction between productivity dispersion and firm competition for workers. I calibrate the model using administrative data covering the universe of firms in Canada from 2000 to 2015. As in the data, most firms have a high labor share, yet the aggregate labor share is low due to the disproportionate effect of a small fraction of large, highly productive firms. I find that a rise in the dispersion of firm productivity causes the aggregate labor share to decline in favor of firm profits. The mechanism is that productivity dispersion effectively shields high‐productivity firms from wage competition. Regression evidence from cross‐country and cross‐industry data supports both the model prediction and mechanism.